Social promotion through two studies of a student with low vision: basic education to university - Oliveira Aguiar, Ana Lucia (2019)
This article is born from a project linked to the research line Educational Practices, Culture, Diversity and Inclusion, carried out by the Pro-Rectory of  Research and Postgraduate Studies (PROPEG) of the State University of Rio Grande do Norte (UERN / BRAZIL). The aim of this study is to understand how the success of a UERN undergraduate student at the popular level and with poor vision has contributed to his social progress from Basic Education to Higher Education. It is a qualitative research, based on Oral History, from (auto)biographical narratives, which allow a formative and self-formative process in the writing of the self and of the other. The access and permanence of the student in his trajectory between Basic Education and the University is a result of the help of the family and the support of the Directorate of Policies and Inclusive Actions (DAIN) of UERN. The lessons learned by the help of the family and by the support of a Multiprofessional Team of the DAIN contribute to the formation of the student, empowering him in the struggle to overcome architectural, physical and attitudinal barriers experienced in social and academic contexts.